Evaluation of Nurses’ Practices toward Safe Intravenous Chemotherapy Infusion in Baghdad City Hospitals - Fadhil, Iman; Hassan, Huda (Iraqi National Journal of Nursing Specialties, 2018)
Abstract Objectives: The study aims to evaluate the nurses’ practices that concerning intravenous chemotherapy infusion and to find out the association between nurses’ practices and their level of education, year of experiences, and training course. Methodology: A descriptive study was conducted in Baghdad Teaching Hospital and Al Amal National Hospital for Treatment of Tumors for the purpose of evaluating the practices of nurses related to infusion of intravenous chemotherapy for the period from 20th October 2017 to 14th March 2018. The sample was randomly selected from both hospitals. Who were evaluated by using a checklist to observe their practices which consisted of two parts; the first part included the demographic information of the nurses and the second part included nursing practices to give intravenous chemotherapy in three domains and 52 items. SPSS version 23 was used to analyze data by applying descriptive analysis (percentages, frequencies and arithmetic mean) as well as inferential analysis (person correlation coefficient and T-test). Results: The results of the study showed that the majority of nurses did not apply proper nursing practices before, during and after chemotherapy, which of 73%, 54%, and 92.3%, respectively, and there is no statistically significant relationship between the educational level and years of service with the nurses’ practices of chemotherapy. Recommendation: The researchers recommend the implementation of continuous training programs for all workers in oncology units which, related to the correct rules in chemotherapy administration and infection control.